Evaluation of pyrolysis characteristics of milled bamboo using near-infrared spectroscopy - Posom, Jetsada; Saechua, Wanphut; Sirisomboon, Panmanas (My University, 2017)
This paper reports the development of a rapid and low-cost method based on near-infrared spectroscopy as an alternative for thermogravimetric determination of the pyrolysis characteristics, including Tonset, Tsh, Tpeak, Toffsetand DTGpeak, of milled bamboo. Tonsetis the extrapolated onset temperature that is calculated from the partial peak resulting from the decomposition of the hemicellulose component, Tshis the temperature corresponding to the overall maximum of the hemicellulose decomposition rate, DTGpeakis the overall maximum of the cellulose decomposition rate, Tpeakis the temperature corresponding to the overall maximum of the cellulose decomposition rate and Toffsetis the extrapolated offset temperature of the DTGpeakcurves determined using thermogravimetric analysis (TGA). The models may be used to control the pyrolysis processes of bamboo to achieve the most economical and environmental conditions. 80 samples of bamboo with various circumferences of culms in the ranges of approximately 16–18, 18–20, 20–22, 22–24, 24–26, 26–28, 28–30, 30–32, 32–34, 34–36, 36–38 and 38–40 cm were randomly collected for optimization of the models. The models were optimized by partial least squares regression (PLSR) with 80% of samples for the calibration set and 20% for the validation set. For Tonset, Tsh, Tpeak, Toffsetand DTGpeakthe models showed coefficients of determination (R2) of 0.566, 0.845, 0.917, 0.973, and 0.671; root mean square errors of prediction (RMSEP) of 9.7 °C, 4.36 °C, 3.77 °C, 2.66 °C, and 0.428 wt loss %/min; ratios of prediction to deviation (RPD) of 1.52, 2.58, 3.48, 3.55, and 1.75; and biases of −0.344 °C, −0.765 °C, 0.349 °C, −5.41 °C, and 0.045 wt loss %/min, respectively. In addition, the results showed that pyrolysis characteristics did not depend on the circumference. The vibrational bands of water and CH3, O[sbnd]H stretch, first overtones of Ar–OH, CH2and HC[dbnd]CH in the cellulose and lignin structures, O[sbnd]H hydrogen bonds of polyvinyl alcohol and C[sbnd]H stretch corresponding to the first overtone of CH2had the highest influence on the values of Tonset, Tsh, Tpeak, and Toffset, respectively. The vibrational band of the C[sbnd]O[sbnd]C asymmetrical stretches of cellulose and hemicellulose, and the combination of O[sbnd]H stretch and HOH bend of polysaccharides influenced the DTGpeakvalue. These results are beneficial for studying the thermal behaviour of milled bamboo as a potential resource for producing biofuels, especially in the pyrolysis process.
Keywords: Bamboo; Near-infrared spectroscopy; Pyrolysis characteristics; Renewable energy; Thermogravimetric analysis